(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Modern sports training involves improving the training process taking into account current scientific achievements. The coach’s ability to explore the possibilities of introducing innovations into the training process becomes important. The purpose of the study is to determine the peculiarities of the formation of research competence of future sports coaches. To achieve the goal, relevant methods of pedagogical research were chosen. As a result, it was established that research competence is a component of the professional competence of a sports coach. Its essence lies in the development of the formation of a set of theoretical knowledge and the development of practical skills that contribute to deepening the understanding of the importance of scientific research methodology for improving the process of training athletes. The components of the research competence of a sports coach are determined. The importance of self-improvement in professional activity is emphasized as a key to the development of research competence. This is achieved by developing analytical skills and the ability to self-reflect. The formation of the research competence of future sports coaches should take into account the motivation for scientific research through the assimilation of theoretical knowledge and practical skills from research work. It is assumed that the acquisition of research competence by the future coach will contribute to the actualization of the implementation of modern scientifically based training methods in the process of training athletes. This will contribute to improving professional competence and increasing the success of coaching activities. Thus, the importance and features of the formation of research competence of future sports coaches have been established, which will allow further formation of programs in special disciplines taking into account modern requirements for quality training of sports coaches.